The Relationship Between Student Learning Types and Indonesian Language Learning Achievement in FTIK IAIN Palopo Students - Firman Firman; Mirnawati Mirnawati; Sukirman Sukirman; Nurul Aswar (Jurnal Konsepsi, 2020)
This study aims to determine the type of learning, achievement and the relationship between the type of learning and student achievement in FTIK IAIN PAlopo students. The population in this study were all students and lecturers of FTIK IAIN Palopo. For this reason, the "Area probolity sampling" technique used in this study by setting classes A and B as a sample of 50 students. The results showed that the types of learning owned by the students of FTIK IAIN Palooo were visual, auditive, and combinative types. The types of learning that most FTIK IAIN Palopo students have is the combinative type (mixed). The learning achievement of FTIK IAIN Palopo students is at an adequate level, which is an average of 7 (seven). The relationship between student learning types and student achievement is a positive correlation. It is said so because the types of student learning and student achievement are not in opposite directions. The obstacles experienced in the teaching and learning process of FTIK IAIN Palopo students to achieve good performance are that lecturers and students are not yet disciplined in carrying out their duties, lecturers have not understood the types of student learning in depth, student interest in learning is still low and the lack of student modules .